Numerical Investigation of Heat Transfer and Phase Change Characteristics of Cold Load and Storage Functional CPB in Deep Mine - Wang, Mei; Liu, Lang; Wang, Shiqi; Lv, Bo; Zhang, Bo; Zhang, Xiaoyan; Zhao, Yujiao; Huan, Chao (Frontiers in Earth Science, 2020)
As high mine-cooling costs have become a restriction for deep mining, a new cooling method has been proposed. In the area of filling mining, the CPB (cemented paste backfill) was given the cooling function by mixing it with phase change material (PCM). In deep mines, the PCM (e.g., ice particles) absorb heat and change phases to cool the surrounding environment. A deep-mine-cooling mode based on the new CPB and upward sublevel filling method was designed, and the characteristics of the phase change were analyzed by numerical simulation. From the simulation results of the cooling period, this cooling method was effective during the whole stopes mining period. The CLS (cold load and storage) CPB mass concentration and the PCM initial proportion are the important factors controlling the cooling effect. It is concluded that the phase change duration decreased with the increasing mass concentration, while it increased with the increasing initial proportion of ice to water. Note that the thickness of CLS-functional CPB should be as small as possible to ensure the cold release rate. This study provides a theoretical foundation of heat transfer for the design and implementation of deep-mine cooling by applying CLS-functional CPB.